The promotion of decentralisation and local governance in fragile contexts - Jörn Grävingholt; Christian von Haldenwang (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
The promotion of decentralisation and local governance has long since been an established part of bilateral and multilateral development cooperation. In the context of fragile statehood, however, this area of development cooperation is frequently faced with the general suspicion of encouraging separatism, exacerbating conflicts, and thereby promoting the disintegration of the state. At the same time, fragile contexts create demand for institutional solutions concerning the distribution of tasks, responsibilities, resources and political power between the various different levels of the state. This paper provides an overview of the challenges regarding support to decentralisation and local governance in fragile contexts. It discusses risks and opportunities, and develops suggestions on how development cooperation can better rise to the challenges surrounding the promotion of decentralisation in fragile states. Against this background the authors advocate an ambitious approach which understands the promotion of decentralisation as being a contribution to overcoming fragility and to the structural alleviation of conflict situations.
Keywords: 330; Governance; Sicherheit; Frieden und fragile Staaten